Analisis Miskonsepsi pada Materi Larutan Penyangga Menggunakan Two-Tier Diagnostic Test - Stephanie, Mian Maria; Fitriyani, Dewi; Paristiowati, Maria; Moersilah, Moersilah; Yusmaniar, Yusmaniar; Rahmawati, Yuli (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This study aims to find out the misconceptions that occur in buffer solution materials using two-tier diagnostic tests instrument. The instrument was developed based on the buffer solution material competency indicators into 10 questions and was declared valid for use. The research was conducted on level I and III college students and students totaling 159. The results showed that there was a misconception on the concept of buffer solution properties of 24.6%, the concept of buffer solution composition was 24.1%, the working principle of buffer solution was 29.3 %, and the concept of pH solution is 25.4%. he cause of the misconception is because the initial concept of the respondent is weak, the teacher's explanation often simplifies the concept, the habit of the respondent to memorize, understanding the language and weak mathematical concepts, and learning models that have not provided the opportunity for respondents to understand the components and principles of working buffer solutions microscopically. Knowledge of misconceptions is needed as an evaluation of teachers and lecturers to be more motivated to implement learning models that are able to overcome misconceptions to prevent wider misconceptions in learning chemistry that make chemistry difficult. Keywords Misconception, Two-Tier Diagnostic Test, Buffer Solution